2019
DOI: 10.1186/s12864-018-5421-3
|View full text |Cite
|
Sign up to set email alerts
|

The genome-wide transcriptional consequences of the nullisomic-tetrasomic stocks for homoeologous group 7 in bread wheat

Abstract: BackgroundHexaploid bread wheat (Triticum aestivum L) arose by two polyploidisation events from three diploid species with homoeologous genomes. Nullisomic-tetrasomic (nulli-tetra or NT) lines are aneuploid wheat plants lacking two and adding two of six homoeologous chromosomes. These plants can grow normally, but with significantly morphological variations because the adding two chromosomes or the remaining four chromosomes compensate for those absent. Despite these interesting phenomena, detailed molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Moreover, we observed strong apparent transcriptional compensation, based on the significantly greater number of upregulated DEGs in wheat compared with the number of downregulated DEGs (Figure 1D). We found that the compensatory transcriptional effects almost all the wheat chromosomes not just incomplete compensation supported by a study using nullisomic-tetrasomic wheat lines (Zhang et al, 2019). Notably, the corresponding homologous chromosomes showed a higher proportion of upregulated DEGs than other chromosomes (Figure 1D).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, we observed strong apparent transcriptional compensation, based on the significantly greater number of upregulated DEGs in wheat compared with the number of downregulated DEGs (Figure 1D). We found that the compensatory transcriptional effects almost all the wheat chromosomes not just incomplete compensation supported by a study using nullisomic-tetrasomic wheat lines (Zhang et al, 2019). Notably, the corresponding homologous chromosomes showed a higher proportion of upregulated DEGs than other chromosomes (Figure 1D).…”
Section: Discussionsupporting
confidence: 77%
“…The W7984 chromosome arm deletion may not have been detected by the larger wheat community, or earlier in our research, in part because of no aberrant morphological variation or infertility, which is characteristic of whole‐chromosome arm deletions (Zhang et al., 2019, 2020). Here, we used a subset of both SynOpDH and SynOpRIL populations to (a) significantly and consistently map QTgw.cnl‐5A across four environments; (b) develop HIFs for fine‐mapping QTgw.cnl‐5A and disrupt linkage disequilibrium (LD) with chromosome arm 5AS presence (+) and absence (−); (c) conduct grain growth rate analysis for greater phenotypic resolution; (d) measure the transcriptome of chromosome arm 5AS+/ QTgw.cnl‐5A + and chromosome arm 5AS−/ QTgw.cnl‐5A− HIFs; and (e) conduct gene ontology (GO) term enrichment analysis.…”
Section: Introductionmentioning
confidence: 73%